Adaptive Method for Power Quality Improvement through Minimization of Harmonics Using Artificial Intelligence - P. Thirumoorthi; Raheni T D (Institute of Advanced Engineering and Science, 2017)
Power system harmonics are a menace to electric power system with disastrous consequence. Due to the presence of non linear load, power quality of the system gets affected. To overcome this, shunt active power filter have been used near harmonic producing loads or at the point of common coupling to block current harmonics. The shunt active power filter is designed to minimize harmonics in source current and reactive power in the non linear power supplies which are creating harmonics. In this paper, Instantaneous power of p-q theory is employed to generate the reference currents and PI controller is used to control the dc link voltage. In addition to this, Artificial Intelligence (AI) technique is used to minimize the harmonics produced by nonlinear load. The main objective of this paper is to analyze and compare THD of the source current with PI controller and by artificial neural network based back propagation algorithm. The proposed system is designed with MATLAB/SIMULINK environment.